Sarcoidosis in Ireland: Regional differences in prevalence and mortality from 1996-2005 - Nicholson, T.T.; Plant, B.J.; Henry, et al., M.T. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: Sarcoidosis is a common multisystem disease of unknown cause and Ireland is among the countries with the highest reported prevalence of disease worldwide. Despite this, reports on the geographical distribution of disease and differences in mortality due to sarcoidosis within Northern Ireland (NI) and the Republic of Ireland (ROI) are currently lacking. Objective: This study was performed to examine sarcoidosis prevalence and mortality in Ireland (NI and ROI) to specifically determine if geographical or temporal clusters of disease are present and if any differences in mortality exist between NI and ROI. Design: A retrospective study, examining hospital discharge data for NI and ROI and data on deaths due to sarcoidosis, obtained from the relevant official government agencies. Results: For 1996-2005, the prevalence of sarcoidosis was 28.13 per 100,000 for ROI compared with 11.16 per 100,000 for NI (p=0.002).Two significant spatial clusters of disease were detected in the Northwest (Prevalence = 44.9 per 100,000) and also the Midlands region (32.1 per 100,000). Two lower-prevalence spatial clusters were also detected in the South and Southeast of ROI. Temporal clustering was also present throughout ROI and NI for the years 2000 to 2004, while space-time clustering was found in three regions, theWest (ROI), the East (ROI) and Northeast (ROI and NI). The case fatality rate for ROI was 0.84%, and for NI was 1.44% (p=0.03). Conclusion: Considerable heterogeneity in disease prevalence is evident in Ireland as significant spatial, temporal and space-time clusters of sarcoidosis are demonstrated in this study. Prevalence rates are also higher than that previously reported for Ireland and are comparable to those of Scandinavian countries. Although case-fatality is low in both ROI and NI, it is significantly lower in ROI. Further study is needed to investigate these findings and the creation of an all-island sarcoidosis registry would provide a mutually beneficial means of capturing this data more effectively.